Wisata Edukasi Mandiri Energi Menggunakan PLTS dan PLTB di Pantai Ria Bomo Kabupaten Banyuwangi - Mulyadi, Adi; Putra, Adi Pratama; Wardhana, Meghandi Gusti; Nalandari, Rezki; Mutowib, Aan (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2022)
Abstract – This paper describes the concept of energy independent educational tourism on Ria Bomo beach, Banyuwangi. Educational tourism is implemented to help the community's economy after the COVID-19 pandemic. The decline in post-pandemic tourists from 35,035 to 689 visitors, so that it has an impact on MSME business actors and tourism managers. Therefore, the community service team proposed the use of natural resources by implementing PLTS and PLTB as an effort to encourage business actors. The application of PLTS and PLTB is conceptualized as an education for tourists visiting Ria Bomo beach. The results of applying the concept show that the increase in tourist visitors is 10% on Monday-Friday. While tourist visitors on Saturday-Sunday to 20%. This concept is applied for education and piloting at beach destinations throughout Banyuwangi Regency.